Erasing Class/ (re)Creating Ethnicity: Jobs, Politics, Accumulation and Identity in Kenya - Mwangi wa Githinji (University of Massachusetts, Department of Economics, 2012)
A large literature on African economies argues that ethnicity plays a role in the politics and economics of African countries. Unfortunately, much of this literature is speculative or anecdotal because of the lack of data, with the exception of a few papers that examine ethnic networking as a business or employment strategy. In many ways Africas failure to develop is a failure of nationhood. Creating nation is handicapped by the use of ethnicity. In this paper, I empirically examine the relationship between employment, wages and ethnicity in Africa via a case study of Kenya. I challenge the pervasive view that ethnicity in Africa is related to a primordial instinct and attempt to show empirically that ethnicity is used by politicians as a political strategy to maintain power. In the process of using ethnicity, class solidarity is explicitly down played by politicians as ethnicity is reified. In this paper I specifically examine whether jobs are being used by politicians as both reward and carrot to ensure ethnic allegiances. This is done by testing whether being a member of a dominant group (in terms of population and also politically) has an impact on the possibility of employment and the level of wages. I do this using data from the 1986 Labour Force Survey which due to timing, uniquely allows me to connect ethnicity and income. I group the observation into 5 groups that are ranked based on kind of employment and wage. Of the five sectors the two desirable sectors are Self-employed above median income and Full time employment above median income. I test whether ethnicity has an impact of one being employed in these sectors. By inter-acting the dummy variable for dominant group in population and the ethnic dummy, I am able to separate out what may be returns just due to ethnic networking that comes from common culture, language etc and returns which are due in some sense to being from a politically dominant ethnicity. I am also able to test for the impact in a change in the ethnicity of the president (a further test of ethnic dominance) by using a difference in difference approach. I find that being in a politically dominant group improves ones chances of obtaining a full time above median wage job. In fact this improvement in chances was highly correlated with political power and a change of ethnicity of the president resulted in a decrease in the probabilities of the past presidents kinsfolk being in desired sectors. Being a member of a locally dominant group in terms of population as compared to a politically dominant national group has no effect on likelihood of employment in one of the premium categories. My findings support the view that in a highly centralized state ethnicity can be reproduced via preferential employment to members of an in-group thus diminishing class solidarity that one may expect to occur between workmates. JEL Categories: Z13 N37, O15, P16.
Keywords: Z13; N37; O15; P16; 330; Social Stratification; Discrimination; ethnicity; Kenya; inequality; class; employment